Effect of Age-Friendly Care on Days at Home Post-Hospital Discharge for Traditional Medicare Patients: A Cross-Sectional Study - Kathleen Drago MD; Bryanna De Lima MPH; Sophie Rasmussen MBA; Alaina Ena RN, MN; Elizabeth Eckstrom MD, MPH; Ella Bowman MD, PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
The Bundled Payment for Care Improvement Advanced (BPCI-A) model encourages value-based care by bundling 90-day healthcare-related costs into a single payment for eligible service codes and procedures for traditional Medicare Part A and B beneficiaries. Our institution, an Age-Friendly Health Systems Level 2 certified academic health center, participated in the BPCI-A model from 2018 to 2022. This study aimed to determine differences in days spent at home in the 30- and 90-day post-hospitalization period for older patients in the BPCI-A program based on Age-Friendly care status. Descriptive analyses assessed differences among patients who received Age-Friendly care (n = 275) and those who did not (n = 348). Zero-one-inflated beta regression models with propensity score matching compared the probability of spending days at home between groups. Sensitivity analyses were conducted. Age-Friendly care recipients tended to be older males with non-emergent admissions and lower risk-adjusted mortality scores ( P  < .05). No significant differences were shown between groups at 30- and 90-days post-discharge for the original analysis. Sensitivity analyses found the probability of spending all eligible days at a facility 30-days post discharge significantly higher for those not receiving Age-Friendly care compared to those receiving Age-Friendly care ( P  < .05). Admissions receiving at least 3Ms resulted in less days in a facility within 30 days of discharge. This highlights the importance of patient-centered and value-based care during the hospital stay. Future studies should continue to explore days at home as a patient-centered outcome measure and how comprehensive Age-Friendly care impacts days at home for a larger cohort.